Ulat Palat, Class 2 - Amra Alam (Bookgroup, 2023)
Ulat pulat,is a poetic exploration by Amra Alam that captures a wide range of emotions and experiences through elegant Urdu verses. The collection is celebrated for its emotional depth and lyrical beauty
Keywords: Textbook, -- Poem